AN ANALYSIS OF IDIOMATIC EXPRESSION TRANSLATION IN SCHOOL OF ROCK MOVIE - Ryan Andhika Pratama; Gheza Damara (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2018)
English native speakers express their feelings and condition using idiomatic expressions. Idiomatic expressions in English cannot be translated literally in the target language. Furthermore, idiomatic expressions translation can be found in movie dialog as a subtitle. This research answers one research problem, which is the idiomatic expressions translation in School of Rock movie. The instruments of this study are the English subtitle and the Indonesian subtitle of School of Rock movie.